XENOPHON'S SOCRATES ON WISDOM AND ACTION. (December 2021) - Bjelde, Joseph
Abstract: Xenophon's Socrates, like Plato's, holds that wisdom comes with practical abilities. But influential interpretations of Xenophon's Socrates attribute to him a splintered view of wisdom, on which there is no wisdom simpliciter which is specially connected to all good actions. This article argues that a crucial text ( Memorabilia 3.9.5) is significantly more problematic for the splintered view than hitherto appreciated, while the texts which are supposed to support the splintered view do not. Instead, this article argues that for Xenophon's Socrates the unwise lack self-knowledge, and so also lack a special prohairetic ability needed for doing fine and good actions.